Effects of sleep modulation during pregnancy in the mother and offspring: Evidences from preclinical research. (2nd July 2020) - Pires, Gabriel Natan; Benedetto, Luciana; Cortese, Rene; Gozal, David; Gulia, Kamalesh K.; Kumar, Velayudhan Mohan; Tufik, Sergio; Andersen, Monica Levy
Abstract: Disturbed sleep during gestation may lead to adverse outcomes for both mother and child. Animal research plays an important role in providing insights into this research field by enabling ethical and methodological requirements that are not possible in humans. Here, we present an overview and discuss the main research findings related to the effects of prenatal sleep deprivation in animal models. Using systematic review approaches, we retrieved 42 articles dealing with some type of sleep alteration. The most frequent research topics in this context were maternal sleep deprivation, maternal behaviour, offspring behaviour, development of sleep–wake cycles in the offspring, hippocampal neurodevelopment, pregnancy viability, renal physiology, hypertension and metabolism. This overview indicates that the number of basic studies in this field is growing, and provides biological plausibility to suggest that sleep disturbances might be detrimental to both mother and offspring by promoting increased risk at the behavioural, hormonal, electrophysiological, metabolic and epigenetic levels. More studies on the effects of maternal sleep deprivation are needed, in light of their major translational perspective.